Watchful Waiting Versus Surgery of Mildly Symptomatic or Asymptomatic Inguinal Hernia in Men Aged 50 Years and Older: A Randomized Controlled Trial. Issue 1 (January 2018) - de Goede, Barry; Wijsmuller, Arthur R.; van Ramshorst, Gabrielle H.; van Kempen, Bob J.; Hop, Wim C. J.; Klitsie, Pieter J.; Scheltinga, Marc R.; de Haan, Jeroen; Mastboom, Walter J. B.; van der Harst, Erwin; Simons, Maarten P.; Kleinrensink, Gert-Jan; et al.
Abstract : Objective: To compare if watchful waiting is noninferior to elective repair in men aged 50 years and older with mildly symptomatic or asymptomatic inguinal hernia. Background: The role of watchful waiting in older male patients with mildly symptomatic or asymptomatic inguinal hernia is still not well-established. Methods: In this noninferiority trial, we randomly assigned men aged 50 years and older with mildly symptomatic or asymptomatic inguinal hernia to either elective inguinal hernia repair or watchful waiting. Primary endpoint was the mean difference in a 4-point pain/discomfort score at 24 months of follow-up. Using a 0.20-point difference as a clinically relevant margin, it was hypothesized that watchful waiting was noninferior to elective repair. Secondary endpoints included quality of life, event-free survival, and crossover rates. Results: Between January 2006 and August 2012, 528 patients were enrolled, of whom 496 met the inclusion criteria: 234 were assigned to elective repair and 262 to watchful waiting. The mean pain/discomfort score at 24 months was 0.35 [95% confidence interval (CI) 0.28–0.41)] in the elective repair group and 0.58 (95% CI 0.52–0.64) in the watchful waiting group. The difference of these means (MD) was −0.23 (95% CI −0.32 to −0.14). In the watchful waiting group, 93 patients (35·4%) eventually underwent elective surgery and 6 patients (2·3%) received emergent surgery for strangulation/incarceration. Postoperative complication rates and recurrence rates in these 99 operated individuals were comparable with individuals originally assigned to the elective repair group (8.1% vs 15.0%; P = 0.106, 7.1% vs 8.9%; P = 0.668, respectively). Conclusions: Our data could not rule out a relevant difference in favor of elective repair with regard to the primary endpoint. Nevertheless, in view of all other findings, we feel that our results justify watchful waiting as a reasonable alternative compared with surgery in men aged 50 years and older. Abstract : Supplemental Digital Content is available in the text